Implementing a South African E-Dispute Resolution System For Consumer Disputes - Reddy, Sershiv (Obiter, 2020)
In the 1990s, online dispute resolution became more prevalent with the growth of the Internet and its accompanying issues. Yet despite the apparent advantages of online dispute resolution platforms, South Africa has lagged behind in using such a system for consumer disputes. It has become necessary to appeal for the use of an online system since courts are often too costly and backlogged with other disputes; and existing consumer mechanisms found in the Consumer Protection Act 68 of 2008 have proved to be ineffectual. With the expansion of artificial intelligence and South Africa now entering the Fourth Industrial Revolution, it is evident that reforms to consumer laws may be necessary to keep up with technological advances, as well as to expedite consumer disputes. The use of an online dispute resolution system powered by artificial intelligence may prove beneficial in South Africa. This article argues for the implementation of an e-dispute resolution system similar to eBay’s online Resolution Center.